Suicide attempt between criminalization and legalization: A comparative study - منجد, منال مروان (Journal of Legal Sciences, 2024)
Hardly a day passes without hearing the news of a person’s suicide here or there, as if life no longer has value for a person, and this fact is what prompted the World Health Organization to sound the alarm, after it found that suicide had become widespread in the world and published its report Under the title (Suicide Prevention - A Global Necessity), and announced the need to take care of mental Health as part of public health, because what psychological human crises are exposed to may lead to suicide.      A quick look at the position of the various legislations on suicide, we find there is a great difference, some legislations recognize the human right to death, while other legislation punishes the mere attempt to commit suicide, and to clarify that we have covered in this research the definition of suicide and its related acts, as we have explained The position of different legislation on it.